MOMENTS OF SAMPLE EXTREMES OF ORDER STATISTICS FROM DISCRETE UNIFORM DISTRIBUTION AND NUMERICAL RESULTS - Calik, Sinan; Bugatekin, Ayse T. (Vinca Inst Nuclear Sci, 2018)
In this study, the mth raw moments of sample extremes of order statistics from discrete uniform distribution are obtained. The results of sample extremes of order statistics of random variable for the independent and identically discrete uniform distribution are given. Numerical values are shown in table form.
Keywords: order statistics; discrete random variables; moments; distribution function